2021
DOI: 10.1007/s12223-021-00922-9
|View full text |Cite
|
Sign up to set email alerts
|

Higher seasonal temperature enhances the occurrence of methicillin resistance of Staphylococcus aureus in house flies (Musca domestica) under hospital and environmental settings

Abstract: Antimicrobial resistance (AMR) emergence in commensal and pathogenic bacteria is a global health issue. House flies (Musca domestica) are considered as biological and mechanical vectors for pathogens causing nosocomial infections, including methicillin-resistant Staphylococcus aureus (MRSA). However, the prevalence of antimicrobial resistance and the role of temperature on the occurrence of Staphylococcus aureus and MRSA in house flies in a hospital environment have not been studied. A total of 400 house flies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…In our study, 61% (61/100) of biofilm-forming S. aureus isolates harbored the methicillin resistance gene, mecA . The standard gold method for detecting MRSA isolates is mecA detection via PCR [ 42 ]; however, in our study, the mecA gene was absent in 39% of S. aureus isolates that were phenotypically MRSA. The inconsistency of the correlation between phenotypic and genotypic resistance of MRSA might be due to the mutation of genes that result in non-functional proteins and the dearth of gene expression [ 43 ].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In our study, 61% (61/100) of biofilm-forming S. aureus isolates harbored the methicillin resistance gene, mecA . The standard gold method for detecting MRSA isolates is mecA detection via PCR [ 42 ]; however, in our study, the mecA gene was absent in 39% of S. aureus isolates that were phenotypically MRSA. The inconsistency of the correlation between phenotypic and genotypic resistance of MRSA might be due to the mutation of genes that result in non-functional proteins and the dearth of gene expression [ 43 ].…”
Section: Discussionmentioning
confidence: 58%
“…The inconsistency of the correlation between phenotypic and genotypic resistance of MRSA might be due to the mutation of genes that result in non-functional proteins and the dearth of gene expression [ 43 ]. In addition, the absence of the mecA gene in the MRSA isolates might be due to the detection methods we used, or those MRSA isolates could harbor other methicillin resistance genes, such as mecB , mecC , or mecD [ 42 ]. Our findings suggest the possible presence of other intrinsic and extrinsic factors having the ability to compete with the mecA gene for developing MRSA.…”
Section: Discussionmentioning
confidence: 99%
“…AMR is a problem for global public health, and when MDR strains appear, bacteria pose a serious threat to healthcare communities [ 62 ]. In this review, 14 out of 17 articles showed MDR E. coli ; among them, the majority of the articles (9/17) reported 100% MDR E. coli in poultry and/or poultry environments.…”
Section: Discussionmentioning
confidence: 99%
“…Isolates having golden-yellow colonies on MSA agar plates were assumed to be S. aureus , and they were sub-cultured on MSA plates to obtain pure colonies. Moreover, the purity of the colonies was checked by culturing on 5% bovine blood agar plates, followed by incubating at 37 °C for 24 h. Presumptive S. aureus colonies were then isolated by Gram staining, Voges–Proskauer tests, glucose and mannitol utilization tests, catalase tests, and coagulase tests [ 13 ].…”
Section: Methodsmentioning
confidence: 99%